D. D. BREZHNEV: A TIRELESS RESEARCHER OF PLANT RESOURCES, EXCELLENT ORGANIZER OF SCIENCE AND INDUSTRY, MENTOR OF SCIENTISTS (CELEBRATING THE 110-ANNIVERSARY OF HIS BIRTH) - V. I. Burenin (Труды по прикладной ботанике, генетике и селекции)
The article describes the life and career of Dmitry Danilovich Brezhnev, N. I. Vavilov’s colleague, scientist of worldwide renown, great organizer of science, who made an undeniable contribution to the development of N. I. Vavilov’s ideas on mobilization, study and use of the world's plant resources.